A study on the ICT intensity and economic resilience of the regional economies of the Philippines lessons from the COVID-19 pandemic - Alicaba, Khristina O.; Catayas, Justine
The growing global focus on economic resilience, particularly in the wake of acute shocks like the COVID-19 pandemic, underscores the critical need to understand factors enhancing a region's adaptive capacity. This study investigates the causal relationship between pre-existing ICT intensity and economic resilience across the 17 regions of the Philippines during the unprecedented disruptions of 2020-2023. Employing a robust Difference-in-Differences econometric approach with panel data from 2018-2023, and supported by extensive robustness checks including fixed effects, lagged variables, and placebo tests, the findings consistently reveal that regions with higher ICT intensity exhibited significantly greater economic resilience. This suggests advanced digital infrastructure served as a crucial buffer, enabling the continuity of vital economic activities through remote work and digital services. However, a nuanced complexity emerges: while ICT provided an immediate advantage, its contribution to sustained, long-term resilience appeared to diminish in the most comprehensive models. This indicates that the full dividends of digitalization may remain untapped without deeper integration into broader economic processes and supportive complementary policies. This research provides compelling causal evidence for ICT's pivotal role in crisis adaptation, emphasizing the imperative for equitable digital access, enhanced literacy, strategic cross-sectoral integration, and context-specific policy frameworks to cultivate truly resilient regional economies.